Praksisnær undervisning i praksis og teori - Nordkvelle, Yngve Troye; Nyhus, Lene; Røisehagen, Anne; Hojem Røthe, Randi (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
"Our students in higher education want their studies to be useful and relevant to their future work career, personal development and social life. The authorities want students' achievements and completion of degrees to increase. Likewise, they expect the workforce to be optimally adapted to today's market and the uncertain demands of the future. They require students to be flexible, willing to learn and familiar with an abundance of general skills. A universal solution is to make studies more ""practical"". We -as teachers in HE - are challenged to improve students' abilities to reason and to prepare for practical applications, whether we are working on conventional theoretical topics in professional education or in continuing education. The authors of this book believe that the work of teaching with these expectations in mind is not just about professional practice, but about practical matters in a broad sense. Students are active in many ways, and they learn and work in the contexts in which they move, so the experiences and insights that they bring with them and then create by acquiring competences also make them practitioners themselves. One of our central educational tasks is to help them to recognize self-worth, that is, to see themselves in the mirror of knowledge, values and skills that higher education can offer them. The book contains examples of how students can work practically and in research, from R&D projects about learning to theoretical contributions. The examples also show how theory and practice can flow together in any teaching environment as well as in the construction of curricula and programmes. "